Contingency in Education: New Conditions and New Mechanisms in Choosing Educational Trajectories - Pavel Stepantsov; Vasily Kuzminov (Voprosy obrazovaniya / Educational Studies Moscow, 2013)
Pavel Stepantsov, M.A. in Sociology (Manchester University), intern researcher at the Centre for Fundamental Sociology, National Research University — Higher School of Economics, Moscow, Russian Federation. Email: pavel.stepantsov@gmail.com    Address: 20 Myasnitskaya St., Moscow, 101000, Russian Federation.Vasily Kuzminov, M.A. in Sociology (Manchester University), intern researcher at the Centre for Fundamental Sociology, National Research University — Higher School of Economics, Moscow, Russian Federation. Email: frameanalysis@ya.ru   Address: 20 Myasnitskaya St., Moscow, 101000, Russian Federation.The paper provides an insight into the market model of educational choice, identifying it as insufficient to explain the way school graduates choose a professional education institution.An opinion poll conducted among schools graduates (9th and 11th grades) and students of vocational technical schools, colleges and higher education institutions has revealed heterogeneity of post-secondary education: there is no single ‘place market’ in this education, no single differentiation system which would enable professional education institutions of different types to ‘scan’ academic performance of candidates.As institutions of each type have their own codes for candidate selection, educational choice of school students is not restricted to choosing an education institution; it also involves choosing the right code recognizable by professional education institution of a specific type. That is why, when the Unified State Exam (USE) was made a universal code for all HE institutions, educational choice of students not interested in higher education was shifted in time from the 11th grade to the 9th grade, as the USE code was not used when applying to vocational technical schools or colleges. By contrast, nearly all 11th graders (90%) are going to apply to HE institutions only—they already made their choice of code when they decided to take the USE.Conclusions reached in the course of this study are used to describe possible patterns of further research on educational trajectories.